GTOC 11: Results found at Beijing Institute of Technology and China Academy of Space Technology. (January 2023) - Lu, Shaozhao; Zhang, Yao; Zhang, Jingrui; Cai, Han; Qi, Rui; Li, Xingang; Qi, Yu; Xiao, Qian; Shen, Ao; Zhang, Tiantian; Zhang, Kunpeng; Ye, Ji; et al.
Abstract: This paper presents the crucial method for the results found at Beijing Institute of Technology and China Academy of Space Technology in the 11th Global Trajectory Optimization Competition (GTOC-11). To build 12 solar-power stations placed in the "Dyson Ring" orbit around the Sun, GTOC-11 focuses on the flyby trajectory design, low-thrust trajectory optimization, and target assignment problem. The mission with time and state constraints causes many difficulties in the design and optimization, which is performed in the following four steps. The first step is to design the orbital elements of the "Dyson Ring" by the grid search method. An approximate model is utilized to evaluate the minimum transfer time for each candidate at first, and the accurate solutions are obtained by the indirect method. The second step involves the Mother Ship trajectories design. A large quantity of earth-to-asteroid and asteroid-to-asteroid subsequences are generated by parallel beam search. The complete trajectories of Mother Ship are designed by connecting the subsequences using beam search. The third step involves the station assignment problem, which is required to design the asteroid transfer device activation epoch and the target station assignment. Based on the results above, the last step involves the rendezvous trajectories optimization to obtain the accurate thrust direction profile. Finally, the submitted and post-competition results are reported. Highlights: The simplified and accurate model are proposed to obtain the optimal transfer time. The parallel beam search is developed to reduce the computational burden. The station assignment problem is solved by coordinate descent method.